2013
DOI: 10.1002/pamm.201310003
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of Carbon Nanotubes

Abstract: We discuss the mechanical properties of carbon nanotubes, in particular the pressure-dependence of the Raman modes and the collapse pressure, and their relation to the corresponding mechanical properties of graphite and graphene. The frequencies of the Raman G-mode and radial breathing mode (RBM), as well as the pressure dependence of the RBM can be largelyexplained in the existing framework of C-C stretching modes and envirionmental effects induced by the pressure medium. The pressure dependence of the G-mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Lastly, for an aspect ratio of 20, both empty and filled (13,0) SWCNT showed first an elastic response reaching small yield strains, followed by an almost constant residual force.The collapse under compressive force of an empty and filled (26,0) SWCNT is illustrated inFigure Four different stages are highlighted, namely, I) the initial, relaxed configuration, II) the system just before it buckles, III) immediately after the structural collapse and IV) the final, fully compressed configuration obtained at 10% strain. A similar buckling behaviour was recently reported from Monte Carlo simulations also for applied hydrostatic pressure[35]. The higher deformability of the empty SWCNT seen inFigure 2provides a clear visual clue of how the yield strength is increased with the inclusion of the ZnS.…”
supporting
confidence: 86%
“…Lastly, for an aspect ratio of 20, both empty and filled (13,0) SWCNT showed first an elastic response reaching small yield strains, followed by an almost constant residual force.The collapse under compressive force of an empty and filled (26,0) SWCNT is illustrated inFigure Four different stages are highlighted, namely, I) the initial, relaxed configuration, II) the system just before it buckles, III) immediately after the structural collapse and IV) the final, fully compressed configuration obtained at 10% strain. A similar buckling behaviour was recently reported from Monte Carlo simulations also for applied hydrostatic pressure[35]. The higher deformability of the empty SWCNT seen inFigure 2provides a clear visual clue of how the yield strength is increased with the inclusion of the ZnS.…”
supporting
confidence: 86%
“…Our experimental and theoretical results for the collapse pressures are collected and compared in Figure 4. We also compare them with the MD and G-band Raman data reported in the literature et al [8] and the DFTB results previously reported for bundled nanotubes without PTM [5] (these are given and for the MC model [29] as well as for DFTB calculations [5]. In the polygon model, the R −3 dependence was observed for all n g -gons, but with a correction term in n g so that the normalised collapse pressure could be written as P N C ≃ 24D(1−β 2 g /n 2 g ) with β g ≃ 5.3 (here β g stands for "geometric β").…”
Section: Discussionmentioning
confidence: 61%
“…In the simulations, armchair and zig-zag nanotubes with diameters up to 5.7 nm were hydrostatically loaded. Some of the collapse pressures were previously reported [29].…”
Section: Modelingmentioning
confidence: 94%
See 1 more Smart Citation
“…The GGA approach used in these calculations provides an improved description of the strong intralayer valence bonds in relation to previous studies based on the local density approximation [37,[42][43][44], and yields frequency values that are in excellent agreement with the experimental results. In the case of graphite, it has been argued that the sublinear pressure dependence of the E high 2g frequency is largely due to the reduced in-plane force on the sp 2 bonds resulting from the large c-axis compression under pressure, which introduces sublinearity in the pressure dependence of the biaxial inplane force [45]. Since the c-axis linear compresibility of h-BN (β 0 = 37.7 GPa, β = 6.3) is comparable to that of graphite (β 0 = 35.7 GPa, β = 10.8), the same effect is expected in h-BN.…”
Section: H-bnmentioning
confidence: 99%